Identifikasi Berat Badan Berdasarkan Citra Foto Menggunakan Metode Body Surface Area - Sten Dofanky Mooy; Andrew Delfistian Dethan; Yampi R Kaesmetan (STIKes Ibnu Sina Ajibarang, 2024)
Measurement of human body weight is an important process in various contexts, such as medical staffing administration, military recruitment, and individual health assessment, as body weight is a key parameter for determining one's body condition. Weight information is traditionally obtained using manual scales, which have been used for many years. However, manual weight measurement is quite time-consuming, especially when done for many people and repeatedly, such as in military recruitment or medical administration. A new approach using digital image technology offers improvements in this process. Therefore, this research aims to calculate human body weight based on digital photos using the Body Surface Area (BSA) method. The use of the BSA method in digital image-based weight measurement involves calculating the body surface area to estimate body mass. This method combines parameters such as height and body circumference taken from the photo image to calculate BSA. Furthermore, an investigation into calculation analysis and accuracy enhancement is conducted. The calculated weight results from the photos are then compared with the scale results to determine their accuracy. Based on the calculation results, an approximate value of 93.3% accuracy is obtained with an average conversion factor of 0.978 at a distance of 300 cm between the camera and the object.